The Effect Of Organizational Culture, Work Discipline And Communication On Performance Of Employees Pt. Persero Batam - Saputra, Deva Giovani; Raymond, Raymond (Universitas Batam, 2021)
This study aims to determine the effect of organizational culture, work discipline and communication on employee performance at PT. Persero Batam. The method used is a quantitative method. The population in this study were employees of PT. Persero Batam with a total of 145 employees. The sample used was 61 respondents. The data collection technique used in this study was through an online questionnaire. The data analysis technique in this study uses Multiple Linear Regression using SPSS version 25 software. The results of this study indicate that Organizational Culture has no significant positive effect on the performance of Pt employees. Persero Batam with a probability value of 0.344 > 0.05. Work Discipline has a positive and significant effect on the performance of Pt. Persero Batam with a probability value of 0.000 < 0.05. Communication has a positive and significant effect on the performance of Pt. Persero Batam with a probability value of 0.012 < 0.05. The value of the coefficient of determination of 59.5% shows the contribution of the influence of organizational culture, work discipline and communication on employee performance at PT. Persero Batam and the remaining 40.5% is explained by other variables.